Simulacra as a Distortion of the Meaning of the Mass for the Dead in the Music Video “Dalam Hitungan” by the Band.Feast - Pasya, Daffa Kamal; Nurliah , Nurliah; Dristiana Dwivayani, Kadek; Muhammad, Harry Isra (Jurnal Indonesia Sosial Sains, 2026)
This study examines simulacra as a form of distortion of the meaning of the ritual of the Soul Mass in the video clip "In Count" by the band. Feast which is released in 2023. This video clip is interesting to study because it presents a representation of religious rituals that is full of visual symbols, but placed in a digital culture context that emphasizes media documentation, visibility, and connectivity. This research aims to understand how simulacra is displayed as a distortion of the meaning of the ritual of the Soul Mass through visual symbols that appear in a series of scenes. The method used is interpretive qualitative research with Roland Barthes semiotic analysis, which includes the reading of denotative, connotative, and mythical meanings. The selection of units of analysis was carried out through Jean Baudrillard's simulacra theory, focusing on ten scenes representing the five aspects of simulacra. The results show that these video clips build on the dominant myth that represents social media and digital connectivity as a new authority in contemporary religious practices. The ritual of the Mass of the Spirits is no longer fully interpreted as a sacred experience that is transcendent, but is reduced to a visual performance that can be recorded, displayed, and socially validated. These findings confirm the existence of a process of desacralization of worship, as well as serve as a social critique of the shift in the religious orientation of the people in today's visual and digital culture.